Budaya Penggunaan Stiker WhatsApp Sebagai Media Komunikasi Humor di Kalangan Mahasiswa - Amanta Fatia Salma; Lina Nafisatussangadah; Riri Izzatur Hasna (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to analyze the culture of using WhatsApp stickers as a medium of humor communication among students of UIN Prof. K.H. Saifuddin Zuhri Purwokerto. This study uses a qualitative approach with observation, in-depth interviews, and documentation as data collection techniques. The research involved five informants from two WhatsApp groups consisting of active university students. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results show that WhatsApp stickers function as a medium for expressing emotions, creating humor, strengthening interpersonal relationships, and simplifying communication in informal interactions. However, the use of stickers also has the potential to create misunderstandings due to differences in interpretation and communication context. Therefore, understanding communication ethics and contextual meaning is important in the use of digital visual symbols among students.